Spectroscopic Study for Determination of Amoxicillin Using Cobalt(II) as Complexing Metal - May M.J. Al-Mudhafar (College of Pharmacy University of Baghdad, 2017)
This study includes analytical methods for the determination of the drug amoxicillin trihydrate (Amox.) in some pharmaceutical preparations using Cobalt ion (Co(II)) as complexing metal. The best conditions for complexation were: the reaction time was 20 minutes, pH=1.5 and the best temperature of reaction was 70 ËšC. Benzyl alcohol was the best solvent for extraction the complex. Keywords: Amoxicillin, Cobalt(II), Complex, Molar ratio.